THE KEY CONCEPTS OF PBL (PROBLEM-BASED LEARNING) IN TEACHING LANGUAGES (Web of Teachers: Inderscience Research, 2024)
There are several reasons driving the shift towards problem-based learning (PBL) in curriculum design. The traditional education system is increasingly viewed as inadequate for contemporary needs. Students frequently experience dissatisfaction and boredom with their learning experiences. They are often required to memorize large volumes of information, much of which appears irrelevant to their future lives beyond the classroom. This lack of perceived relevance leads to a decline in motivation. Unmotivated students tend to exhibit disruptive behaviors and increased absenteeism. Furthermore, they retain little of what they have learned, and even the knowledge they do retain is not easily applied to real-world challenges and tasks they encounter later.